A comparative study of safety and efficacy of tiotropium bromide with salbutamol in moderate persistent bronchial asthma in a tertiary care hospital - S, Vijaya; N, Rajyalakshmi; B, Ramanath (International Journal of Research in Medical Sciences, 2017)
Background: The objective of this study was to compare the safety and efficacy of tiotropium bromide with salbutamol in moderate persistent cases of bronchial asthma at tertiary care hospital. Methods: This was an open label, randomized parallel group study done in Government General Hospital, Srikakulam for a period of 12 weeks. Group-1 was given tiotropium bromide metered dose inhalational therapy 18mcg once daily in 50 patients. Group-2 was given salbutamol metered dose inhalational therapy 100mcg thrice daily in 30 patients. Results: Symptomatic improvement was observed in l two groups. At end point, mean FEV1 in tiotropium bromide treatment group improved by 149.96% compared with 135.16% salbutamol treatment group. At end point, mean FVC value in tiotropium bromide treatment group improved by 145.71% compared with 122.34% in salbutamol group. Mean FEV1 / FVC also improved by 155.41% in tiotropium bromide group compared with 105.41 % in salbutamol group. Conclusion: The present study proved tiotropium provide superior safety and efficacy relative to control drug in bronchial asthma patients in both clinical assessment score and spirometrically.